Folds--Offshore of Tomales Point Map Area, California - S.R. Hartwell; S.Y. Johnson; M.W. Manson (USGS Science Data Catalog, 2014)
This part of DS 781 presents data for folds for the geologic and geomorphic map of the Offshore of Tomales Point map area, California. The vector data file is included in "Folds_OffshoreTomalesPoint.zip," which is accessible from http://pubs.usgs.gov/ds/781/OffshoreTomalesPoint/data_catalog_OffshoreTomalesPoint.html. The Point Reyes Peninsula is bounded to the south and west in the offshore by the north- and east-dipping Point Reyes Thrust Fault (McCulloch, 1987; Heck and others, 1990), which lies about 20 km west of Tomales Point. Granitic basement rocks are offset about 1.4 km on this thrust fault offshore of Point Reyes (McCulloch, 1987), and this uplift combined with west-side-up offset on the San Andreas Fault (Grove and Niemi, 2005) resulted in uplift of the Point Reyes Peninsula, including Tomales Point and the adjacent continental shelf. Grove and others (2010) reported uplift rates of as much as 1 mm/yr for the south flank of the Point Reyes Peninsula based on marine terraces, but reported no datable terrace surfaces that could constrain uplift for the flight of 4-5 terraces exposed farther north along Tomales Point. Folds were primarily mapped by interpretation of seismic reflection profile data (see field activity S-15-10-NC). The seismic reflection profiles were collected between 2007 and 2010. References Cited Grove, K., and Niemi, T.M., 2005, Late Quaternary deformation and slip rates in the northern San Andreas fault zone at Olema Valley, Marin County, California: Tectonophysics, v. 401, p. 231-250. Grove, K, Sklar, L.S., Scherer, A.M., Lee, G., and Davis, J., 2010, Accelerating and spatially-varying crustal uplift and its geomorphic expression, San Andreas fault zone north of San Francisco, California: Tectonophysics, v. 495, p. 256-268. Heck, R.G., Edwards, E.B., Kronen, J.D., Jr., and Willingham, C.R., 1990, Petroleum potential of the offshore outer Santa Cruz and Bodega basins, California, in Garrison, R.E., Greene, H.G., Hicks, K.R., Weber, G.E., and Wright, T.L., eds. Geology and tectonics of the central California coastal region, San Francisco to Monterey: Pacific Section, American Association of Petroleum Geologists Bulletin GB67, p. 143-164. McCulloch, D.S., 1987, Regional geology and hydrocarbon potential of offshore central California, in Scholl, D.W., Grantz, A., and Vedder, J.G., eds., Geology and Resource Potential of the Continental Margin of Western North America and Adjacent Oceans Beaufort Sea to Baja California: Houston, Texas, Circum-Pacific Council for Energy and Mineral Resources, Earth Science Series, v. 6., p. 353-401.